Improving Madrasah Ibtidaiyah Teacher Job Satisfaction Through Madrasah Compensation and Facilities - Sri Rahayu; Ferdinand Salomo Leuwol; Siti Nurida; Suyitno Suyitno; Ari Kartiko (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study has the aim of finding loopholes and digging up information about the problem of job satisfaction which is influenced by several factors including compensation and facilities, there are two problem formulations that limit the discussion so that it does not widen, namely analyzing teacher job satisfaction (Y) which is influenced by compensation (X1 ) and facilities (X2) partially, while the second question is to analyze teacher job satisfaction (Y) which is affected by compensation (X1) and facilities (X2) simultaneously. The research method used is quantitative using survey methods. The data used is primary data obtained directly from 32 respondents using a questionnaire. The questionnaire used has tested the validity and reliability tests. The research data analysis technique used multiple linear regression tests and carried out F tests and T tests. The results showed that compensation and facilities had a positive effect on teacher job satisfaction at Madrasah Ibtidaiyah Mambaul Khoir Talang partially or simultaneously.Stakeholders need to pay attention to the provision of compensation both financially and non-financially so as to increase teacher job satisfaction.